Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.analchem.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glycosylation on the Comparability of the Higher-Order Structures in Idursulfase by Hydrogen–Deuterium Exchange Mass Spectrometry

Abstract: Characterization of the higher-order structures in idursulfase (iduronate-2-sulfatase, I2S) has been accomplished through the use of hydrogen−deuterium exchange mass spectrometry (HDX-MS). The method has over 97% sequence coverage, including seven of the eight glycosylation sites, and has been used to study the impact of glycosylation on backbone proton exchange. In addition, the method adapted a well-used biophysical spectra comparison method (similarity scoring) to define quantitative acceptance criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. 548 551 In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. 541 , 552 Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
See 1 more Smart Citation
“…In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. 548 551 In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. 541 , 552 Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…Even with limited sequence coverage, HDX-MS has been a reliable tool for mapping binding interfaces and tracking structural changes upon protein–protein and protein–ligand interactions involving serum glycoproteins ,, and receptors. ,,, Several studies have also used HDX-MS to assess the influence of glycosylation itself on the overall structure of serum glycoproteins with some interesting variability that reveals a complex relationship between a protein’s glycosylation state and its conformational dynamics. In some systems, HDX-MS showed mixed effects with some areas becoming stabilized and other regions showing increased accessibility upon glycan removal. In other glycoproteins, the only observed changes were increased dynamics through the protein upon glycan removal. , Some studies observed only very minor changes in HDX kinetics despite known effects on overall thermal stability upon glycan removal . The available studies have thus far revealed a complex and very context-dependent relationship between glycosylation and structural dynamics.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…HDX-MS has an important role in understanding conformation/dynamics changes driven by post-translational modification. , To date, there are two examples of subsecond time-resolved HDX-MS being used specifically to examine changes in conformational dynamics due to post-translational modification. In the first, Zhu, Wilson, and co-workers examined the impact of phosphorylation on the binding specificity of the intrinsically disordered N-terminus of the apoptosis modulator protein (and key cancer target) p53 .…”
Section: Time-resolved Ms In Protein Dynamicsmentioning
confidence: 99%
“…HDX-MS can also be used to detect how different glycosylations can impact the overall structure of a protein. One recent study was able to distinguish the subtle changes that occur in the idursulfase enzyme when glycosylation sites were modulated [ 71 ]. This can have significant applications in the pharmaceutical industry, as monoclonal antibodies produced by different manufacturing processes often have differing glycosylation patterns.…”
Section: Applications Of Hdx-msmentioning
confidence: 99%